Variasi Pelapis Luar dan Berat Labur Perekat Phenol Formaldehida terhadap Kualitas Papan Lamina dengan Inti dari Batang Kelapa Sawit - Rasi Odesto Tarigan; Tito Sucipto; Rudi Hartono (Program studi Kehutanan USU, 2015)
Laminated board of oil palm trunk made with variations outer layer plywood 3 mm (P1), plywood 6 mm (P2), and high density of oil palm trunk (BT) with the configuration which is P1-BT, P1-P1, P1-P2, P2-BT, and P2-P2. In addition, by using a variation of phenol formaldehyde adhesive glue spread between 240g/m2 and 260g/m2. The maturation of the adhesive is done using a hot press with a temperature of 150 oC for 15 minutes. This study used a completely random experimental factorial design with 2 factors and the results were compared with the JAS 243:2003 standard.The results of this study among others density, water content, water absorption in immersion for 2 hours and 24 hours, thickness swelling on immersion for 2 hours and 24 hours, delamination ratio, MOE and MOR were 0,48-0,62 g/cm3, 9,73-11,36%, 23,55-33,57% and 72,62-85,27%, 3,64-8,64% and 8,32-15,04%, 0%, 31.402-47.533 kg/cm2 and 254,17-374,25 kg/cm2. Water content, the ratio of delamination and largely MOR value fulfilled JAS 243:2003 standard.The best of outer layer and phenol formaldehyde adhesive glue spread by JAS 243:2003 standard and results of the analysis range for the laminated board with oil palm trunk as a raw materials in general was P2-BT (plywood 6 mm and high density of oil palm trunk) and glue spread was 260 g/m2.Keywords: laminated board, oil palm trunk, outer layer, glue spread, phenol folmaldehyde.